How has Covid-19 re-shaped the medical technology industry - Cruz, Felipa Val Bento (2022)
COVID-19 has challenged the MedTech industry causing disruptions on supply chains, delayed, or cancelled clinical trials and product launches and a drop in elective medical procedures amongst other obstacles. The purpose of this work project is to analyze the challenges that the pandemic put the industry through, the strategic responses to a crisis and the opportunities it created through its disruption. The research employs an analysis, for which three semi-structured interviews with experts within the field were conducted. The findings reveal the responses taken by MedTech firms and provide lessons that can be applied to future crises.